Creating Sustainable Competitive Advantage using Resource Based Review: Case study of Citigroup - Pang, Shay (2007)
This report shall focus on the creation of sustainable competitive advantage in Citigroup based on the Resource Based View approach. The main motivation behind this research is to understand what constitutes to Citigroup SCA from its humble beginnings as a small local bank to the world largest bank today. Through this research, I hope to unravel some of these possible sources of SCA in Citigroup.